2014
DOI: 10.1186/1756-3305-7-370
|View full text |Cite
|
Sign up to set email alerts
|

Shaping zoonosis risk: landscape ecology vs. landscape attractiveness for people, the case of tick-borne encephalitis in Sweden

Abstract: BackgroundIn this paper, the hazard and exposure concepts from risk assessment are applied in an innovative approach to understand zoonotic disease risk. Hazard is here related to the landscape ecology determining where the hosts, vectors and pathogens are and, exposure is defined as the attractiveness and accessibility to hazardous areas. Tick-borne encephalitis in Sweden was used as a case study.MethodsThree boosted regression tree models are compared: a hazard model, an exposure model and a global model whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
47
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 30 publications
(41 reference statements)
1
47
0
Order By: Relevance
“…As in Zeimes et al (2014), explanatory variables were allocated to hazard or exposure, but some were included in both classes ( Table 1). …”
Section: Independent Variablesmentioning
confidence: 99%
See 3 more Smart Citations
“…As in Zeimes et al (2014), explanatory variables were allocated to hazard or exposure, but some were included in both classes ( Table 1). …”
Section: Independent Variablesmentioning
confidence: 99%
“…Linard et al (2007) also pointed out the significance of adding variables related to human behaviour and land use in addition to land cover and habitat variables in epidemiological models. Moreover, Zeimes et al (2014) showed that a model considering hazard and exposure offers better predictive power than models considering only hazard or exposure.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…The landscape also affects the spatial distribution of human activities and thus contacts between susceptible humans and infected ticks (9). Complex and fragmented landscapes provide more ecotones (transition area between two adjacent biomes) and can increase contacts between species associated with diverse habitats, including reservoir hosts and ticks, and increase accessibility to forests (10, 11). Furthermore, landscape fragmentation can influence biodiversity (12).…”
mentioning
confidence: 99%